2017
DOI: 10.3389/fphar.2017.00548
|View full text |Cite
|
Sign up to set email alerts
|

DAF-16/FOXO Transcription Factor in Aging and Longevity

Abstract: Aging is associated with age-related diseases and an increase susceptibility of cancer. Dissecting the molecular mechanisms that underlie aging and longevity would contribute to implications for preventing and treating the age-dependent diseases or cancers. Multiple signaling pathways such as the insulin/IGF-1 signaling pathway, TOR signaling, AMPK pathway, JNK pathway and germline signaling have been found to be involved in aging and longevity. And DAF-16/FOXO, as a key transcription factor, could integrate d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
123
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(131 citation statements)
references
References 85 publications
2
123
0
Order By: Relevance
“…Anti‐microbial proteins also exhibit a second set of potential lifespan effectors in C. elegans. Previous study has shown that gene encoding for anti‐bacterial lysosomes ( lys‐7 ) is upregulated in daf‐2 null mutant, which can also upregulate during Serratia marcescens pathogenic infection (Sun, Chen, & Wang, ). Metallothionein (MT) is a low molecular weight anti‐apoptotic protein that has been shown to scavenge free radical involving stress sensitive pathway in C. elegans and mice.…”
Section: Discussionmentioning
confidence: 99%
“…Anti‐microbial proteins also exhibit a second set of potential lifespan effectors in C. elegans. Previous study has shown that gene encoding for anti‐bacterial lysosomes ( lys‐7 ) is upregulated in daf‐2 null mutant, which can also upregulate during Serratia marcescens pathogenic infection (Sun, Chen, & Wang, ). Metallothionein (MT) is a low molecular weight anti‐apoptotic protein that has been shown to scavenge free radical involving stress sensitive pathway in C. elegans and mice.…”
Section: Discussionmentioning
confidence: 99%
“…DAF-16 plays a role in both oxidative and heat stress as well as starvation. It is the sole orthologous of the FOXO family of transcription factors in C. elegans and DAF-16/FOXO proteins are a family of transcription factors that integrate different signals by phosphorylation of proteins including insulin/IGF-1, TOR, AMPK, or JNK pathways to modulate important processes, via shuttling from cytoplasm to nucleus, and the expression of genes that influence in cell growth, proliferation, differentiation, or longevity 25 . Under these circumstances, cytosolic DAF-16 protein is phosphorylated and then it relocates to the nuclei and promotes both the expression of genes that confer resistance to stress and longevity.…”
Section: Effect Of Xanthigen® On Daf-16 Translocation Hsp-162 and mentioning
confidence: 99%
“…This transcription factor is involved in diverse cellular function including the regulation cell death or apoptosis, resistance to oxidative stress and increased life span. Good references for the regulation of these transcription factors are available [54][55][56]. Hence, transcription factors that are critically involved in alleviation of oxidative stress and increased life span of C. elgans are activated by D. indusiata polysaccharides.…”
Section: Antioxidant Effectmentioning
confidence: 99%